Thoracoscopic S6 segmentectomy: tricks to know - Seguin-Givelet, Agathe; Lutz, Jon; Gossot, Dominique (Video-Assisted Thoracic Surgery; Vol 1 (October 2016): Video-Assisted Thoracic Surgery, 2016)
Thoracoscopic S6 segmentectomy is a relatively easy sublobar resection. However, there are many variations in the anatomy that can make the procedure more difficult than expected. Some technical difficulties can also be faced. This article is based on an experience of 68 S6 segmentectomies, 40 left and 28 right, out of a series of 272 thoracoscopic sublobar resection. In 2 cases, the S6 segmentectomy was extended to S2 and to S10. Indication was a proven or suspected cT1aN0 non-small cell lung carcinoma in 48, suspected metastasis in 11 and benign lesion in 9 patients. There were 4 conversions into thoracotomy (5.9%). Mean operative time was 137 mn (range: 50–240 mn) and mean intraoperative blood loss was 82 cc (range: 0–700 cc). Mean drainage duration was 2.6 days (range: 1–8 days) and mean hospital stay was 4.8 days (range: 2–10 days). Based on our experience, the aim of this article is to illustrate variations and suggest technical tips that make the procedure reliable and reproducible.